(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The government and courts use the death sentence to punish offenders, safeguard the rights ofvictims, and remove potentially dangerous persons from society so they won’t commit another crime. Thisfacet of civilization has existed since the Stone Age, when kings were viewed as the personification of lawand order in the community. The repercussions of a death sentence are irreversible and cannot beundone. The most individuals are executed annually in China. In India, the death sentence is reserved forpeople who have committed the worst crimes. To contradict or support a claim, the author uses reliableand objective sources, data, and subject matter experts. As proof for the researcher’s conclusions, thestudy gives instances and quotations. The study follows a doctrinal pattern, drawing on previouslyaccessible data and analysing those facts to develop an evolution of this research. Primary data consistsof interviews and surveys, whereas secondary data includes publications, laws, parliament bills, andreports. The goal is to understand the Indian death sentence and India’s stance on the issue from aglobal viewpoint. The secondary purpose is to discover alternatives to the death penalty.